Thermal and energy performance of nanofluid operated heat recovery exchanger / Leong Kin Yuen - Leong, Kin Yuen (2013)
In recent years, there has been a substantial increase in energy demand due to industrialization. This raises concern on issues such as depletion of fossil based energy and emission of green house gasses. It is reported that a high portion of industrial energy is wasted as flue gas/hot gas from heating plants, boilers, etc. Hence, optimization of energy use through heat recovery device is one of the possible approaches to address this problem. However, conventional heat transfer fluids feature low thermal conductivity. The development in nanotechnology has enabled the introduction of nanofluids as a new generation of heat transfer fluid. Nanofluids are suspensions of nanoparticles in a base fluid. The inclusion of nanoparticles into a base fluid significantly increases the thermal conductivity of the base fluid. This study attempts to investigate the thermal and energy performance of a shell and tube heat exchanger and thermosyphon airpreheater operated with nanofluids. It focuses on recovering waste heat from hot gases/ flue gas produced by a heating plant. The analysis was conducted based on the thermophysical properties of nanofluids obtained from literatures, mathematical correlations and present experimental data. The thermo-physical properties measured in this study include thermal conductivity, viscosity and density. The study reveales that, the thermal conductivity of ethylene glycol/water based Al2O3 (0.5vol.%, partice size: 13nm) increases about 8.9% compared to base fluid. About 12.9% augmentation is also observed for water based Al2O3 (0.5vol.%, particle size :13nm). Thermal conductivity of nanofluids increases with the increase of particle volume percentage or decrease of particle size. Viscosity and density also show increasing trend with the addition of nanoparticles. The thermal performance of shell and tube heat recovery exchanger improved with the addition of nanoparticles. About 7.8% heat transfer augmentation was observed for the ethylene glycol-based nanofluids containing 1 vol.% of copper nanoparticles at 26.3 kg/s flue gasses’ mass flow rate and 111.6 kg/s coolant’s mass flow rate. For water containing 2 vol.% of copper, 4.5% heat transfer enhancement was recorded. At constant coolant mass flow rate, lower pumping power is needed when nanofluids are applied. About 10.99% less power was observed at 1vol. % of copper nanoparticle compared to ethylene glycol base fluid.The study on the size reduction of heat exchanger, implied that nanofluids provide opportunity to reduce the size of heat exchanger without decreasing its thermal performance. Analysing the total dimensionless entropy generation revealed that, 10.8% reduction is observed with an addition of 7 vol.% of Al2O3 into water. About 9.7% reduction is observed for water-based TiO2 (4 vol.%) nanofluid. Other factors that influence total dimensionless entropy generation are dimensionless temperature difference, fluid mass flow rate, tube diameter and length. Moreover, the study revealed that the change of nanofluid thermo-physical properties only plays a minor role in improving the thermal performance of the thermosyphon heat exchanger. Slight increase of overall heat transfer coefficient and cold air outlet temperatures are observed with increasing nanoparticle volume fraction. However, the thermal performance of thermosyphon heat exchanger increases when the hot air velocity elevates from 2.5 to 4.75m/s.